Profile analysis, treatment methods and strategies adopted by cardiopathy participants for cardiovascular rehabilitation in Vale do Taquari (Research, Society and Development, 2023)
Introduction: Cardiovascular diseases (CVD) are characterized by a set of disorders that affect the heart and blood vessels. They are the main causes of morbidity and disability worldwide. Cardiovascular rehabilitation (CVR) is the main strategy for the treatment of CVD. Objective: The purpose of this study is to analyze the profile, form of treatment and strategies adopted by cardiac patients for CVR in the Vale do Taquari region. Methodology: The study is quantitative, explanatory, of documentary design and cross-sectional cohort, conducted in the first semester of 2021. The study has as reference cardiopathic individuals 18 years old and over who were submitted to cardiovascular procedures at Bruno Born Hospital between January 2018 and December 2020. The subjects were selected through the hospital’s medical records database. Data collection took place in two moments. The first step consisted of analyzing medical records, while the second step consisted of applying a questionnaire composed of questions involving the history of diseases and knowledge about CVR. Participants who agreed to participate consented upon acceptance of the TCLE. Results: The sample, which was selected from non-random convenience through a medical database of Bruno Born Hospital (HBB), in Lajeado RS, was composed of 66 participants, being 51 males (77.3%) and 15 females (22.7%), with an average age of 62.479.84 years. It was found that the main procedures performed were angioplasties with coronary and peripheral “stents” (50%), myocardial revascularization surgery (16.7%), and valve prosthesis implantation (16.7%). More than half of the subjects were not referred to CVR (60.6%). The main forms of treatment were the use of medications (69.7%), followed by follow-up with a cardiologist (68.2%), and the practice of physical exercises (54.6%). Regarding physical exercise, 40.9% of the participants considered themselves sedentary before the procedure, however, after performing the procedure, only 13.6% are still considered sedentary. Conclusion: The data collected indicate that less than half of the subjects investigated underwent some type of CVR. Thus, the CVR area seems to be of great potential for the work of the Physical Education professional.